The waiting list as an instrument, rationalizing access to health care benefits - Jacek, Anna; Kędzior, Klaudia; Porada, Sławomir (Polish Journal of Public Health, 2013)
Introduction. In the system of universal health insurance, a patient cannot expect unlimited access to health care, therefore, the right to use a reliable procedure, being based on medical criteria and determining order of access to health care benefits, has become a key issue. This solution is described as a waiting list for health care benefits.Aim. Becoming acquainted with opinions on the role of waiting list as an instrument rationalizing access to benefits in the system of universal health insurance.Material and methods. The study involved 300 people, making use of health care benefits in therapeutic entities, in the area of Jaroslaw. The goal of this study was achieved by means of the author’s questionnaire.Results. It was shown that 68% of the respondents were not able to find a better solution than keeping waiting list, regarding the access to services funded from the public means. And 32% of them believed that keeping waiting list was pointless, as service providers did not follow the rules of doing it.Conclusions. It was stated that a form of giving information about appointed date of health care benefit provision should be standardized by creating one kind of form that would be given to every patient (on their first visit) at the moment of being signed in waiting list for health care benefits. Patient’s knowledge of using sources of information about waiting time for particular health care service is highly demanded